Diuretic Activity of Various Herbs in India: A Mini Review - Shaikh, Sufiyan Yusuf; Shaikh, Aftab Tanveer; Shaikh, Moinuddin Arif (Borneo Journal of Pharmacy, 2023)
One of the primary uses of medicinal plants is as a diuretic. Both mono- and polyherbal-based diuretic formulations have been used in various parts of the world, including in India. One estimate states that more than 650 mono- and polyherbal formulations are in clinical use, including decoctions, tinctures, pills, and capsules made from over 75 plants. Many studies have been conducted supporting the diuretic properties of conventional herbal remedies. This article discusses many herbal plants from India that have historically been used as diuretics and identifies the chemical components with diuretic activity. In addition, this brief review also discusses several plant drugs and their pharmacological profile, concentrating on the administered dose and the bioactive extracts involved in the diuresis process. For researchers, searching for the best therapeutic plants for diuretic research may be a significant turning point in using various herbs from India.